2019
DOI: 10.3389/fphar.2019.00932
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Disorders in Chronic Kidney Disease

Abstract: Neuropsychiatric conditions including depression, anxiety disorders, and cognitive impairment are prevalent in patients with chronic kidney disease (CKD). These conditions often make worse the quality of life and also lead to longer hospitalizations and higher mortality. Over the past decades, some hypotheses have tried to explain the connection between CKD and neuropsychiatric disorders. The most common hypothesis is based on the occurrence of cerebrovascular disease and accumulated uremic toxins in adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 117 publications
5
52
0
3
Order By: Relevance
“…We found that male participants had significantly higher creatinine than females in the ASD-P, which was in accordance with the fact that creatinine is usually higher in men than in women (29). Although urinary creatinine level is also closely related to kidney function and psychiatric disorders and depression, anxiety and cognitive disorders are common in patients with kidney diseases (30,31), creatinine levels between ASD-P and the Control were comparable among participants in this study. Therefore, creatinine was not considered as a biochemical indicator of psychological or physical problems caused by kidney function disorders among parents of autistic children.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that male participants had significantly higher creatinine than females in the ASD-P, which was in accordance with the fact that creatinine is usually higher in men than in women (29). Although urinary creatinine level is also closely related to kidney function and psychiatric disorders and depression, anxiety and cognitive disorders are common in patients with kidney diseases (30,31), creatinine levels between ASD-P and the Control were comparable among participants in this study. Therefore, creatinine was not considered as a biochemical indicator of psychological or physical problems caused by kidney function disorders among parents of autistic children.…”
Section: Discussionsupporting
confidence: 87%
“…It was the first time that NO metabolites were precisely reported in the parents of children with autism. In order to better understand the role of NO in the ASD-P population, we also provided demographic information for parents in the ASD-P group (43), their children (31), participants in the Control group (43) and participants in the Control group (40) (Supplementary Tables 5, 6).…”
Section: Serum Nitrate In the Asd-p And S-control Groupsmentioning
confidence: 99%
“…Possible consequences of modifications to health resources on accessibility and reliability and performance of psychiatric services throughout the COVID-19 pandemic ( 16 ). Phobic anxiety, impulse purchase, and television addiction, all linked to psychological disruptions, insomnia, exhaustion, and consciousness deterioration, have been documented, and digital networking has been linked to heightened anxiety and depression-associated anxiety ( 17 19 ).…”
Section: Interaction Between Covid-19 and Psychological Well-beingmentioning
confidence: 99%
“…One in five adults with CKD in the US suffers from depression. Patients on dialysis have a higher prevalence of depression and a higher risk of hospitalizations due to psychiatric dysfunction compared to their pre-dialysis and post-transplant counterparts [3]. Behavioral factors such as the burden of self-care decreased day-to-day functionality, and the psychological impact of having a chronic illness also contribute to developing depression [4].…”
Section: Introductionmentioning
confidence: 99%